How long should we fear? Long-term risk of venous thromboembolism in patients with traumatic brain injury. - Olubode, O; Yorkgitis, B; Metcalfe, D; Rios Diaz, A; Haider, A; Havens, J; Cooper, Z; Kelly, E; Gates, J; Salim, A (Lippincott, Williams andamp; Wilkins: No Hybrid Open Access, 2016)
Venous thromboembolism (VTE) constitutes an undesirable outcome in the care of trauma patients. In the United States, the annual healthcare costs associated with VTE is estimated at $1.5 billion(1) and close to 100,000 people die from VTE yearly.(2) Among trauma patients who develop pulmonary embolism (PE), mortality is as high as 19%.(3) These data highlight the significant health burden that VTE exerts on the healthcare system. It is therefore important to identify patients that are higher risk for developing these complications and institute measures to prevent the occurrence of VTE among them.